From Theory to Practice: A Reflective Internship Account in International Education Consultancy - Alina Alam; Ana Yuliana Jasuni (Westscience Press, 2026)
Internship experiences have been acknowledged as essential tools in facilitating transitions between academic education and professional practice, but there is limited literature on such transitions, specifically concerning internships for international education consultancy in Southeast Asia. Therefore, this study seeks to explore how academic knowledge about business management was transferred to professional practice, how major issues encountered during the internship were managed reflectively, and what effect this experience had on shaping professional identity and career orientation. A reflective inquiry research methodology was adopted, using insights derived from the researcher's ten-month internship program at MoveAbroad Indonesia in Jakarta from March 2025 to January 2026, using Morris's (2020) modified framework of experiential learning and Schon's (as cited in Pegg, 2014) reflective learning cycle comprising reflection-in-action and reflection-on-action. The results have shown that reflection on professional experience plays a vital role in enhancing the process of translating academic knowledge into skills. The domains found to be most productive for learning were those associated with B2B marketing based on CRM, student advising, and multicultural team working. Therefore, it is evident that internship programs, when conducted reflectively, can efficiently serve as bridges between academic preparation and professional preparedness, as well as promote the development of professional identity.